An adaptive low power schedule for wireless sensor network - Wan Nor Shuhadah, Wan Nik; Nor Aida, Mahiddin; Almamoon, Alauthman (2021)
A Wireless Sensor Network (WSN) is used in many applications such as remote monitoring and tracking, healthcare, industrial settings, automated and self-adjusting systems at homes and factories. In these systems, energy consumption is a major concern as most devices in the network rely on small batteries for energy source. In such cases, minimization of energy usage can prolong the lifetime of sensor’s battery. Therefore, this paper proposed a strategy to improve the efficiency of power consumption in WSN by decreasing the number of idle listening state which further reduces power consumption. By doing this, it is expected that network life time can be prolonged. Undoubtedly, large amount of energy is wasted in idle listening state. We intelligently improved the original TPO technique in order to achieve less power consumption. The experiments is conducted by using Omnet++ 4.6 with Mixim library and the results showed that when compared with the original TPO technique, the proposed technique achieves significant energy saving which is up to 39.3% better than the original TPO technique.